PENGARUH LATIHAN LOMPAT DI PASIR TERHADAP TINGGI LOMPATAN PADA PEMAIN VOLI INDOR PADA CLUB PUTRA MATARAM TAHUN 2016 - Jamaludin Jamaludin (Universitas Pendidikan Mandalika, 2017)
The game of volleyball is a game played by two teams against each other by passing the ball over the net. The problem in this research is still the lack of leaping the players son of mataram caused by weak leg muscle power. The problem formulation in this research is whether there is influence of jumping exercise in sand to high jump on volleyball player at club of Putra Mataram Year 2016 ?. The purpose of this research is to know whether or not there is influence of jumping exercise in sand to high jump on indor volley in club Putra Mataram Year 2016. The research method used in this research is by experimental method. The research design used is One group pretest-postes design and data analysis techniques using the t-test formula. From the results of data analysis found that, t-count more> t-table (8,276> 2,145) with significant tarap 5% with db = N-1 = 15-1 = 14. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So it can be concluded that there is an effect of jumping exercise in the sand against the high jump on indor volleyball player in club Putra Mataram Year 2016